Emergent hydrogen bonding in dense LiOD. Issue 3 (6th January 2022) - Ridley, Christopher J.; Bull, Craig L.; Funnell, Nicholas P.
Abstract : Lithium hydroxide transforms to an extensively hydrogen-bonded structure under applied pressure. The first direct structural evidence of this is presented. Abstract : We report the first full-structural analysis of two ambient temperature phases (II, III) of LiOD as a function of pressure, and present a direct-structural confirmation of a hydrogen-bonded network in the high-pressure phase-III. LiOD has been measured using neutron powder diffraction up to a maximum pressure of 4.1 GPa. The sample is observed to transform from tetragonal phase-II ( P 4/ nmm ) to phase-III at a pressure of 1.16(3) GPa. The previously suggested monoclinic structure of phase-III, isostructural with NaOD, is shown to strongly misfit the measured data, while a new tetragonal structure ( I 41 / acd ), suggested in the literature from a first-principles calculation, is found to fit the pattern extremely well. Neutron diffraction data from this new tetragonal structure agree with earlier spectroscopic evidence for a hydrogen-bonded network within the system. This tetragonal structure has not been observed in any other alkali-metal hydroxide before now. Details of the hydrogen bond lengths, lattice strains through the transition, and the compressibility of each phase are presented. This revised structure may have implications as to how LiOD is used for high-pressure/high-temperature materials synthesis.